An Efficient Algorithm for Load-Flow Solution of Radial Distribution Networks - Murari, Krishna (My University, 2014)
In this thesis, a new method has been proposed for load-flow calculation of radial distribution systems. The aim of this thesis is to propose a method to identify the nodes beyond each branch with lesser computation. Matrix method has been used in this work to find branch currents, node voltages and power loss in a radial distribution network. The matrix reduces computational time and the solution converges in lesser number of iterations. Simple equations have been used. Effectiveness of this method has been tested on 33- bus and 69- bus radial distribution systems with constant power (CP), constant current (CC), constant impedance (CZ) composite and exponential load modelling. The proposed method converges well for constant power, constant current, constant impedance, composite and exponential load modelling. The superiority of proposed method has compared with existing methods [8,26,27] in terms of relative values CPU time and memory size. The proposed method requires much less time to converge and also require less memory size when compared with the existing methods [8,26,27].
ME, EIED
Keywords: Load-flow, Radial; composite, Exponential; distribution network; convergence rate